Mechanical Loading and Tribological Studies on Boron Carbide (B4C) and Lead (Pb) Particles Dispersed Epoxy-Based Multilayered Composites - S. Vignesh; J. T. Winowlin Jappes; Khan M. Adam; Temal Varol (Advances in Materials Science and Engineering)
The study aims in the development of functionally graded epoxy-based layered composites dispersed with B4C and lead particles. The development route adopted for the composites is a novel route called layered molding and curing. Various compositions of single and trilayered composites were prepared through the abovementioned route. The samples prepared were subjected to mechanical and tribological studies, and the results were reported in this article. It is found that the mechanical properties of the single-layered composites consisting of 20% lead and 20% B4C show superior characteristics than those of the samples with increased addition of lead. However, the trilayered samples with lead core showcased excellent mechanical properties. On the other hand, the wear rate and mass loss of the trilayered samples with B4C cladding show minimum wear rate than the samples with lead cladding. Furthermore, the coefficient of friction of the samples also showcases the better performance of single-layered samples with 20% lead. The worn surface analysis done through scanning electron microscopy and stereo zoom microscopy reveals the reason for the low specific wear rate of 20% lead sample as the self-hindrance of wear debris evolved during the wear study.